Keanekaragaman, Kerapatan, dan Tutupan Lamun Di Pulau Pari, Kepulauan Seribu - Baga, Sisean; Taufiqurahman, Taufiqurahman; Aqil, Deden Ibnu; Florensia, Aurora; Pratiwi, Lidya (INSTITUT AGAMA ISLAM NEGERI AMBON, 2022)
Pari Island is located in Thousand Islands Administrative District, DKI Jakarta Province, with its status as a tourist area, research, and coastal ecosystem conservation. This research is aimed to determine the diversity, abundance, and the seagrass cover located in Pari Island. The method used is a survey with straight transects and quadrants in three different stations, which consist of Pantai Bintang (station 1), Perawan (station 2), and Rengge (station 3). The data analysis towards seagrass diversity uses Shannon-Wiener’s Diversity Index, the seagrass density uses Di calculation, and the seagrass cover uses the seagrass cover index (C). Based on the research conducted, there were 3 seagrass species, which were Enhalus acoroides, Thalassia hemprichii, and Cymodocea rotundata. The highest H’ Index with the value of 2.0 is station 1, which is categorized as mid diversity criteria and the lowest with the value of 0.8 is station 2, which is categorized as low diversity. The highest seagrass density is Enhalus acoroides located in station 1 with the value of 165 (ind/m2) and the lowest which is Cymodocea rotundata located in station 3 with the value of 18 (ind/m2). The best seagrass cover value is in station 1 with the value of 55%, which is categorized as less healthy and the worst cover is station 2 with the value of 21%, which is categorized as poor. Keywords: Diversity, Density, Pari Island, Seagrass Cover